Yakuza Grey: the shrinking of the il/legal nexus and its repercussions on Japanese organised crime - Baradel, Martina (Global crime, 2021)
For decades Japanese criminal syndicates, collectively known as the yakuza, enjoyed a highly visible and semi-legal status that positioned them in a grey area. Accordingly, also much of the yakuza’s business lies in a grey zone: night-entertainment, different forms of gambling, front companies and (fake) social movements. However, following the introduction of new stricter regulations, the yakuza are struggling to keep operating in the legal and semi-legal areas of their business, and have been pushed to explore new modi operandi, using (semi)legal actors and loopholes. Based on fieldwork conducted in Japan with current and ex-yakuza members, this paper analyses the yakuza’s response to the reduced opportunities to engage in legal activities. It is argued that this determined an increased involvement with predatory crimes for low-ranking members, while the decreased power in controlling markets allowed for the emergence of novel forms of crime.